The Effectiveness of Using Padlet in Writing Skills of The English D1 Program for Engineering Students at The University of Muhammadiyah Gresik - Cahyani, Risya Astrifiya; Asmara, Candra Hadi; Rochmah, Noviatul (Journal of English Teaching, Literature, and Applied Linguistics, 2026)
This study investigates the effectiveness of Padlet in improving writing skills for industrial engineering students in the English for Specific Purposes of the English D1 program at the University of Muhammadiyah Gresik. The research involved 50 students from the industrial engineering program. An explanatory sequential mixed-method design was used, combining a quasi-experimental approach for quantitative data collection and interviews for qualitative data. This design was chosen to assess Padlet’s impact on students’ writing skills. The findings reveal that Padlet is an effective tool for enhancing writing skills. The Mann-Whitney test result is 0.000, which is below 0.05, indicating the rejection of the null hypothesis and acceptance of the alternative hypothesis, confirming Padlet’s effectiveness. Interview results further support this, as all participants agreed that Padlet significantly improves their writing skills. Additionally, the study found that Padlet primarily enhances students’ skills in organization and content; Padlet’s user-friendly features also facilitate the learning process. These features allow students to collaborate, organize ideas, and refine their writing effectively. Overall, the research demonstrates that Padlet is a valuable tool for improving writing skills in the students of the English D1 program, particularly in crucial aspects of writing.